DESEMPEÑO LABORAL DE LOS EMPLEADOS DEL GOBIERNO AUTÓNOMO DESCENTRALIZADO (G.A.D) MUNICIPAL DE BABAHOYO EN EL ÁREA DE AVALÚOS Y CATASTRO - Diaz Hidalgo, Silvia Elizabeth (2019)
The present investigation was carried out in the Municipal Autonomous Decentralized Government of the Babahoyo canton, this institution is in charge of providing welfare to the citizens of said canton, through the execution of previously planned activities, implementing programs that contribute and guarantee good living. The Appraisals and Cadastre area is responsible for generating, collecting, managing and updating the information of citizens who participate in the activities that take place in the square to be investigated.